Job satisfaction and gender differences in university employees' attitude toward labour union (2014)
University labour unions are seen as powerful in Nigeria. Most of the industrial actions they embark upon on behalf of members have successfully brought about improvement on members conditions of service. But what is rarely understood is the university employees' attitude toward their unions and the possible roles played by individual and job factors. The study involved a survey design with sample size of 240 purposively drawn from staff members in the three main unions at the Univers ity of Ibadan. Results showed that female staff have more favourable attitude toward unions than their male counterparts. Similarly, those who indicated higher level of job satisfaction also reported more favourable attitude toward unions. Finally, the non-academic members of staff showed more favourable attitude toward their union than the academic staff. It was concluded that female members of staff, those higher on job satisfaction, and non-academic members of staff have more favourable attitude toward labour union. A major implication is that apart from the non-academic staff members being more cohesive, labour unions can promote their effectiveness by having females take up leadership positions. It was therefore concluded that there is the need to encourage females to take up leadership positions in university labour unions, while the academic staff union also need to learn from its non-academic counterpart on strategies for building cohesion among members which results in favourable attitude toward their union. Despite the major contribution in providing insight to attitude toward university's labour unions, future studies in the area should be encouraged to broaden the scope in order to enhance generalization of findings